Successful Embolization of a Large Vein of Galen Malformation in a Premature Infant Presenting with Congestive Heart Failure and Persistent Pulmonary Hypertension - Ashraf M. Aly; Clarisa Y. Garcia; Rudiger von Ritschl (Thieme Medical Publishers, Inc., 2012)
We report a case of a premature infant with a vein of Galen malformation (VGM) who presented with high-output heart failure, pulmonary hypertension, and respiratory distress. An echocardiogram showed normal cardiac anatomy, patent ductus arteriosus, and retrograde flow in the descending aorta. Ultrasonography and computed tomography of head confirmed the diagnosis of a large VGM. The patient developed multiorgan failure. Endovascular embolization of the VGM was successfully performed with an excellent outcome.